Veterinary Treatment of Sheep and Goats - Duncanson, Graham R (CABI, 2014)
The author hopes this book will be useful to veterinary practitioners throughout the world who are treating sheep and goats. Obviously there are some differences between wool sheep and hair sheep, and between dairy goats and meat production goats. These differences will be noted in the text. Each species will be described separately with cross-references where help- ful. Sheep will be described first in each chapter, followed by goats. Where common names are given for plants, these are generally the names that are used in the UK, but some relate to plants from the USA or Australia. Veterinary science is evolving at an ever-increasing rate and so some of this information may be out of date before publication. The author apologizes for this and for any inaccuracies. He hopes that these can be corrected in future editions and would be very grateful for any contact from readers via e-mail to vetdunc@btinternet.com.